New forms of investment (NFI) in Latin American-United States trade relations - Kuwayama, Mikio (UN. ECLAC SantigaoCL, 1992)
Focuses on the complex nature and form of United States-Latin American trade relations and the process of intra-regional specialization, by examining major variants of United States corporate strategies namely, Foreign direct investment (FDI), new forms of investment (NFI) and preferential schemes. Demonstrates that there is a common element among the three, since in each, one can observe an increasing volume of transactions which are essentially production-sharing or overseas sourcing operations. Argues that in spite of a notable increase in Latin American exports of manufactures to the US stimulated by them, ample potential benefits provided by NFI are not yet fully exploited.